Diabetes risk assessment with Indian Diabetes Risk Score: A cross-sectional study among adults in rural Mandya, Karnataka - Shashikantha SK,; Sheethal MP,; Chandana S, (Asian Journal of Medical Sciences, 2024)
Background: Screening for diabetes using the Indian Diabetes Risk Score (IDRS) is an inexpensive yet effective way of early diagnosis. Aims and Objectives: The present study was conducted to assess the risk of developing diabetes among individuals in rural field practice areas using IDRS. Materials and Methods: A community-based observational study was conducted among persons aged 20 years and older in the rural field practice area for 2 months. A semi-structured interview schedule, including the “IDRS” questionnaire, was used to obtain the data. Results: Out of 1100 subjects, around 50% were above 50 years, only 38.6% of the subjects had a waist circumference within the normal limits; 73.8% did moderate exercise; 86% of the subjects had no history of diabetes in their parents. The mean IDRS score of the subjects was 44.12±14.33, ranging from 10 to 90. Nearly 2/3rd (69.6%) of them were at moderate risk, and 21.2% were at high risk for developing diabetes. The IDRS score was significantly higher among those with diabetes and hypertension. Conclusion: The majority of the subjects in our study had a moderate to high risk of developing diabetes as per the IDRS.